(untitled) (Bioresearch Communications, 2021)
Objective: The significance of appropriate infant and young children feeding (IYCF) to ensure proper nutrition for children is well-documented. Although nutrition interventions with agricultural components have the potential, the evidence for this relationship is insufficient. The objective of this study was to evaluate the effects of an integrated health-based intervention on the dietary pattern and nutritional status of children under two years of age. Methodology: This study was a pre-post analysis of secondary data of the project titled “Integrated Agriculture and Health-Based Interventions for Improved Food and Nutrition Security in Selected Districts of Southern Bangladesh”, which were collected from Barisal and Khulna district. We used data of 268 children aged 0-23 months from baseline and 554 children from endline which comprised the study population to assess socio-demographic, anthropometric and IYCF indicators. Further, horticulture, cooking and hygiene indices were created to analyze the effectiveness of the project interventions. Results: A significant reduction of stunting and underweight and insignificant reduction of wasting were observed from baseline to end line. Compared to baseline, the horticulture index, hygiene index and cooking index differ significantly between the baseline and end line surveys. Further, significant improvement of 6 months exclusive breastfeeding and insignificant improvement of continued breastfeeding up to 1 year were found from baseline to end line. Conclusion: This study shows that integrated agriculture and health-based interventions with nutrition components have a positive impact on stunting and underweight but exert a mixed effect on wasting and IYCF practices. Bioresearch Commu. 8(1): 1077-1087, 2022 (January)